Overcrowding a threat to environmental safety and wellbeing: an empirical investigation of female undergraduate halls of residence in a Nigerian university (2016)
Abstract: The demand for University education in Nigeria has led to an increase in undergraduate population and this comes with various problematic conditions with regards to university accommodation, available basic infrastructure and facilities. The resultant effect is manifested in overcrowded residential halls and rooms. Against this backdrop, this study investigated the correlation between overcrowding and environmental safety and wellbeing in female undergraduate halls of residents in the University of Ibadan, Nigeria. Four research questions and two hypotheses guided the study. Descriptive survey research design was adopted and a sample of six hundred and fifty five (655) was proportionately drawn from the residential female undergraduate population of 3274. A questionnaire with reliability coefficient of 0.87 was used for data collection. The results showed that 87.7% of the female undergraduates perceived their rooms to be overcrowded. Findings on environmental safety showed that apart from fire extinguisher, other safety facilities and equipment are either not readily available or are not adequate in all the halls of residence. The result of the hypothesis showed a strong negative relationship between overpopulation and environmental safety and wellbeing. In recommendation, more halls of residents should be built to meet up with the increase in female undergraduate enrolments to Nigerian universities. Environmental safety issues of residential undergraduates must be taken seriously by providing functional safety facilities and equipment to make the halls more secure.